C and UNIX : tools for software design - Barrett, Martin L.; Wagner, Clifford H. (Chichester ; New York : John Wiley and Sons, 1996)
Basic program syntax and control. Program design and control of input/output. Data structure design and management. Advanced features of C and Unix.
Keywords: C; UNIX; Computer program language; C (Computer program language); UNIX (Computer file); Computer software -- Development